Determinants of Mean Blood Pressure and Hypertension among Workers in West Africa - Bosu, William K. (Int J Hypertens, 2016)
Background. This review was undertaken to estimate the mean blood pressure and evaluate its determinants as well as the determinants of hypertension among workers in West Africa. Methods. In a follow-up to an earlier study, a systematic search for articles published between 1980 and August 2015 was undertaken using major databases. Results. A total of 55 articles involving 34,919 different cadres of workers from six countries were retrieved. The mean systolic blood pressure (BP) ranged from 116.6 ± 1.3 mmHg to 151.7 ± 13.6 mmHg while the mean diastolic BP ranged from 69.6 ± 11.0 mmHg to 97.1 ± 9.1 mmHg. Population-wide prehypertension was common. The major determinants of mean BP and hypertension were similar and included male sex, older age group, higher socioeconomic status, obesity, alcohol consumption, plasma glucose, and sodium excretion. Ethnicity and educational level were inconsistently associated with hypertension. Workers at higher risk of cardiovascular event did not perceive themselves as such. Conclusion. The prevailing mean prehypertensive BP, low perception of risk, and clustering of risk factors call for interventions such as healthy diets, improved physical activity, and a favourable work environment. Successful models for improving the cardiovascular health of sedentary informal sector workers in Africa are urgently needed.